Strategi Pengembangan Manajemen Agrowisata Gunungsari Kopeng - Maria Damai Milleni Rosari Leisubun; Damara Dinda Nirmalasari Zebua (Syntax Corporation, 2023)
The tourism sector is a source of income for a country. This is an opportunity that can be exploited by people who want to develop tourism, one type of tourism that is currently developing is agro-tourism. Agro-tourism is a type of tourism the presents the beauty of the agricultural sector in which it is taught how to manage the agricultural sector. One of the tourist destinations that wants to be developed is Gununsari Kopeng Agrotourism which is owned by Mr. Slamet Buang. The purpose of this study was to find out (1) know the strengths, weaknesses, opportunities and threats that Gunungsari has and (2) to formulate and develop appropriate management strategies for Gunung Sari Kopeng agro-tourism. This research was conducted from September to October 2022. The respondents selected were Mr. Slamet Buang as key informant, Irfanianto as informant 1, and Mahmuda Alfitria as informant 2. This study used SWOT analysis. From the results of this study obtained an IFAS value of 0.34 and an EFAS of 1.05 indicating that the management development strategy for Gunungsari Kopeng agro-tourism is quadrant I, namely Progressive (Growing and Developing). Gunung Sari Agrotourism uses the SO (Strength-Opportunities) strategy, namely having a supportive and strategic location and good promotion. With this strategy, Gunung Sari Agrotourism must also pay attention to the lack of water availability and improve the financial and management management system and find out what makes Agrotourism customers disappointed, thus Gunung Sari Agrotourism will grow and develop